Investigating Malaysian Youth’s Social Media Usage, Competencies and Practice with regard to Crime Prevention: An Application of the Social Media Literacy Model - Ahmad, Jamilah; Ismail, Nurzali; Nasir, Nur Nasliza Arina (2015)
According to the statistics, majority of social media users in Malaysia are youth aged 13-34. They use the medium on a frequent basis and at an extended period of time to serve different important functions including for communication, socialisation, building and maintaining relationship, overcoming loneliness, sharing of information, learning and entertainment. There is no doubt of the usefulness of social media, but, the medium also presents risks to youth. On the social media sphere, youth are exposed to risks such as scam, sexual harassment, pedophile, pornography and cyberbullying. Earlier studies also reported that the number of crime cases reported involving youth’s social media practices are on the rise in Malaysia. One way to reduce threat of committing high-risk behaviours and becoming victim on social media is by having adequate level of social media competencies. Such competencies also enable youth to effectively use social media to help the authority in preventing crime. But the question is; what is the level of Malaysian youth’s competencies of social media? Do they use social media to help the authority in preventing crime? In order to answer these questions, a survey involving 500 respondents was conducted to investigate Malaysian youth’s social media usage, competencies and practice with regard to crime prevention.